Handbook of research on tribology in coatings and surface treatment - Pakseresht, Amir Hossein, 1981-; Sharifahmadian, Omid, 1987- (Advances in chemical and materials engineering (ACME) book series., 2022)
"This book evaluates the latest advances in applying the coatings and surface treatments by different techniques to reduce the damages from tribology, giving readers more detailed information to compare the capability of each coating process in wear resistant and lubrication applications"--